Analisis Sistem Informasi Pabrik Piknik Dodol menggunakan Metode SWOT - Ayu Sayyidatun Nisa; Yopi Nugraha (RISTEC : Research in Information Systems and Technology, 2025)
The development of information technology encourages companies to improve the effectiveness and efficiency of their business processes through the implementation of appropriate information systems. This study aims to analyze the condition of the information system at the Dodol Picnic Factory using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method as a basis for formulating information system development strategies. This research employed a qualitative descriptive approach, with data collected through observations, interviews, and documentation studies. The collected data were analyzed using the SWOT matrix to identify internal and external factors affecting the implementation of information systems within the company. The results indicate that the Dodol Picnic Factory possesses strengths in its well-established product quality and extensive industry experience. However, the company still faces weaknesses in the utilization of information technology, which has not yet been optimally integrated. Furthermore, opportunities arising from the advancement of digital technology and the increasing adoption of online marketing can be leveraged to enhance the company's competitiveness, while industry competition and changing market demands represent potential threats that need to be anticipated. Based on the SWOT analysis, the study recommends the development of an integrated information system to support data management, operational activities, marketing, and decision-making processes, thereby improving organizational performance and competitive advantage.